Роль зеленої економіки в сталому розвитку міст - Мельник, Степан Миколайович; Melnyk, Stepan Mykolayovych (Ірпінь, 2023)
Дослідження базується на визначенні особливостей «зеленої економіки», яка дасть змогу вийти із екологічної кризи, підвищить конкурентоспроможність української економіки та істотно вплине на наявний ринок праці. Розроблено аналіз стану розвитку «зеленої економіки» у м. Запоріжжя, визначено перспективу розвитку «зеленої економіки» в контексті забезпечення сталого розвитку.

The study is based on the definition of the features of the "green economy", which will make it possible to get out of the environmental crisis, increase the competitiveness of the Ukrainian economy and significantly affect the existing labor market. An analysis of the state of development of the "green economy" in the city of Zaporizhzhia was developed, and the perspective of the development of the "green economy" in the context of ensuring sustainable development was determined.
The role of the green economy in the sustainable development of cities
Keywords: зелена економіка; сталий розвиток; зелене місто; ресурсоефективність у містах; green economy; sustainable development; green city; resource efficiency in cities